Transnational crime : trafficking in antiquities - Mackenzie, Simon (Henry Stewart Talks, 2008)
Antiquities looting, Effect on source countries, Archaeological concerns, International market, Regulation at source and in the market, International conventions, Codes of practice, Customs controls, Laws in market countries prohibiting dealing in stolen property, Transaction norms in the market, The grey market, Trafficking mechanisms, Case law, The internet, Corruption
Archived at 2022/04/03